Identification of sources from which doctors in the private sector obtain information on HIV and AIDS - Panjasaram Naidoo; Champaklal C. Jinabhai; Myra Taylor (South African Family Practice)
Background: Doctors need to constantly update their knowledge and obtain information in order to practise high-quality medicine. Antiretroviral drugs have been available only since around 1996, therefore many of the doctors who were trained prior to 1996 would not have received any formal training in the management of HIV and AIDS patients. Where doctors source their general medical knowledge has been established, but little is known about where doctors source information on HIV/AIDS. This study investigated where private sector doctors from the eThekwini Metro obtain information on HIV and AIDS for patient management.